Valuation of O2 Czech Republic entities after infrastructure spin-off - Šťastný, David (2015)
This thesis focuses on valuating the newly created companies rendered by the infrastructure spin-off of the Czech telecommunication incumbent O2. The study includes market outlook, analysis of recent performance of the antecedent company and description of the demerger. This is followed by separate valuations of both entities using the two-stage DCF method. The thesis concludes with an analysis of the discrepancy between equity value and its market price together with an elaboration on management's and shareholders' motives and circumstances associated with the spin-off.